Designing a Sulfur Vacancy Redox Disruptor for Photothermoelectric and Cascade-Catalytic-Driven Cuproptosis–Ferroptosis–Apoptosis Therapy - Mengshu Xu; Jingwei Liu; Lili Feng; Jiahe Hu; Wei Guo; Huiming Lin; Bin Liu; Yanlin Zhu; Shuyao Li; Elyor Berdimurodov; Avez Sharipov; Piaoping Yang (Nano-Micro Letters)
Highlights The glycometabolism and enzyme activity of Cu2MnS3-x-PEG/glucose oxidase (MCPG) achieve a cascade catalytic reaction, continuously replenishing the deficient H2O2 and O2 and inducing adequate reactive oxygen species supply. Density functional theory calculations indicate that Mn doping facilitates the structural reconstruction and evolution of sulfur vacancies (SV) sites, leading to a remarkable increase in the catalytic activity of Cu2MnS3-x. Under 1064 nm laser irradiation, MCPG with abundant SV drives charge carrier diffusion from hotter to cooler regions, thus creating a potential difference and activating the photothermoelectric catalysis.